Interactions between subunits a and b in the rotary ATP synthase as determined by cross‐linking. Issue 7 (14th February 2013) - DeLeon-Rangel, Jessica; Ishmukhametov, Robert R.; Jiang, Warren; Fillingame, Robert H.; Vik, Steven B.
Abstract : The interaction of the membrane traversing stator subunits a and b of the rotary ATP synthase was probed by substitution of a single Cys into each subunit with subsequent Cu 2+ catalyzed cross‐linking. Extensive interaction between the transmembrane (TM) region of one b subunit and TM2 of subunit a was indicated by cross‐linking with 6 Cys pairs introduced into these regions. Additional disulfide cross‐linking was observed between the N‐terminus of subunit b and the periplasmic loop connecting TM4 and TM5 of subunit a . Finally, benzophenone‐4‐maleimide derivatized Cys in the 2–3 periplasmic loop of subunit a were shown to cross‐link with the periplasmic N‐terminal region of subunit b . These experiments help to define the juxtaposition of subunits b and a in the ATP synthase. Abstract : ► Interactions of subunits a and b of the rotary ATP synthase were examined. ► Cys substitutions were used for disulfide formation or with a bi‐functional reagent. ► Cross‐linked products indicated that one b subunit has contact with TM2 of subunit a . ► Additional cross‐links were detected between subunits a and b and between b and c . ► A model is presented in which one b subunit is near a TM2 and the other is near a TM5.